Effects of pH, temperature and storage on the stability of MJ-30 protein isolated from Mirabilis jalapa L leaves - ., Sudjadi; Ikawati, Zulies; ., Sismindari; Rahayu, Putu Riana Suastari (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2004)
The total protein of Mirabilis jalapa L leaves had the ability to cleave supercoiled DNA and showed toxicity on HeLa and Raji cell-lines. The 30 kD protein (MJ-30) purified by cationic exchange chromatography possessed activites as RIP e.g DNA supercoiled cleavage and RNA N-glycosidase activity. The aim of this study was to prepare pure MJ-30 and to observe the stability of MJ-30 .MJ-30 of M.jalapa L leaves was purified using the combination of ammonium sulphate fractionation and cationic exchange chromatography with NaCl gradient elution. MJ-30 was subjected for its stability to assays against pH, temperature, and storage period.Stability assay showed that MJ-30 is stabil at pH 5-6, then the activity decreased as the pH increased. This protein was stable at 300 â 550C, and the activity decreased when the temperature increased. Storage at 40C, MJ-30 was stable until 12 days but the activity was decreasing. However, at 300C, MJ-30 was stable for 3 days only. Glycerol addition to the MJ-30 solution has made the activity stable for 18 days at 40C and 300C storage.Keyword : Protein MJ-30, Leaves of Mirabilis jalapa L, stability, pH, temperature, storage